The Evolving Role of 18F-FDG PET/CT in Diagnosis and Prognosis Prediction in Progressive Prostate Cancer - Shen, Kai; Liu, Bo; Zhou, Xiang; Ji, Yiyi; Chen, Lei; Wang, Qi; Xue, Wei (Frontiers in Oncology, 2021)
Positron emission tomography/computed tomography (PET/CT) is widely used in prostate cancer to evaluate localized tumor burden and early detect symptomatic metastatic lesions. 18F-FDG is the most used tracer for oncologic imaging but has limitations in detecting the early stage prostate cancer. 68Ga-PSMA is a new tracer that has high specificity and sensibility in detecting local and metastatic tumors. But with the progression of prostate cancer, the enhancement of glucose metabolism in progressive prostate cancer provides a chance for 18F-FDG. This review focuses on PET/CT in the detection and prognosis of prostate cancer, summarizing literature on 18F-FDG and 68Ga-PSMA in prostate cancer and highlighting that 18F-FDG has advantages in detecting local recurrence, visceral and lymph node metastasis compared to 68Ga-PSMA in partial progressive prostate cancer and castration-resistant prostate cancer patients. We emphasize 18F-FDG PET/CT can compensate for the weakness of 68Ga-PSMA PET/CT in progressive prostate cancer.